2013
DOI: 10.1007/s00508-013-0421-4
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal template-guided biopsy for diagnosis of prostate cancer in patients with at least two prior negative biopsies

Abstract: A 24-core TPB is a safe procedure with a high PCa detection rate. Few of the detected PCa are clinically insignificant. Men with at least two negative transrectal biopsies may be counseled to undergo TPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…We found 39 retrospective studies, 46 prospective studies, and 13 RCTs where periprocedural antibiotics were administered [12] , [13] , [14] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , …”
Section: Evidence Synthesisunclassified
“…We found 39 retrospective studies, 46 prospective studies, and 13 RCTs where periprocedural antibiotics were administered [12] , [13] , [14] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , …”
Section: Evidence Synthesisunclassified
“…However, this approach is still offered in only a small percentage of patients, in particular in conjunction with pre-biopsy MRI, as shown by an audit carried out on behalf of Urological Society of Australia and New Zealand [ 6 , 7 ]. Despite this, several previous studies have confirmed its usefulness in men with previous negative biopsies [ 4 ].…”
Section: Introductionmentioning
confidence: 98%
“…Transperineal route of needle biopsies under guidance of a TRUS probe is emerging as a second line investigation in the diagnostic care pathway, particularly in men with previous negative biopsies and rising PSA [ 3 ]. The burgeoning interest in this approach is due to improved sampling of anterolateral part of the gland, better information on grade and volume of cancer and perhaps a reduced risk of infection compared to transrectal route [ 4 , 5 ]. However, this approach is still offered in only a small percentage of patients, in particular in conjunction with pre-biopsy MRI, as shown by an audit carried out on behalf of Urological Society of Australia and New Zealand [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Сатурационная промежностная биопсия, по мнению многих авторов, обладает преимуществом при повторном исследовании, частота обнаружения РПЖ ва-рьирует от 22,7 до 58% [21][22][23].…”
Section: Discussionunclassified